Performance Analysis of the Regional House of Representatives (DPRD) of Kaur Regency for the 2024–2025 Period - Henny Aprianty; Tudisman Tudisman; Rahiman Dani; Heru Purnawan; Rio Putra Handika (Journal of Social and Policy Issues, 2026)
This study critically evaluates the legislative performance of the Regional House of Representatives (DPRD) of Kaur Regency in formulating regional regulations (Perda) during the 2024–2025 period. While prior studies predominantly focus on procedural compliance, this research addresses the critical gap concerning the substantive effectiveness of local representative institutions in balancing administrative mandates with democratic responsiveness. Employing a qualitative-analytical approach, this study synthesizes primary data from in-depth interviews with key stakeholders, including legislative leaders, secretariat officials, and community representatives, with official documentation and non-participatory observation. The analytical framework utilizes indicators of productivity, responsiveness, and accountability as proposed, grounded within the perspective of Responsive Law, to assess the quality of the legislative process. The findings reveal a significant dissonance between formal procedural adherence and substantive legislative quality. Although the DPRD has successfully met administrative milestones stipulated by Law Number 23 of 2014, the enactment of regional regulations lacks depth in public participation and fails to adequately accommodate community aspirations. Institutional performance is constrained by systemic challenges, specifically the dominance of political interests over public needs, limited technical capacity in legal drafting, and weak transparency mechanisms. Ultimately, this study concludes that DPRD legislative performance in Kaur Regency remains at a moderate level, characterized by high procedural compliance but low substantive impact. To strengthen democratic governance, the institution must shift its orientation from mere administrative fulfillment toward enhancing institutional professionalism, fostering inclusive public consultation, and reinforcing objective policy analysis. This research contributes to public administration scholarship by providing empirical evidence on the limitations of local legislative effectiveness within decentralized governance systems.